Government revenue, 1793-1815 - O'Brien, P (1967)
The thesis began as a study and evaluation of the methods employed by the British Government to finance the wars against France from 1793-1815. Public finances of the late 18th and early 19th centuries is such a neglected field by economic historians that secondary sources on the operation of the financial system scarcely exist. Yet in order to understand the finance of war it is essential to comprehend the whole financial system. Thus a large part of the thesis will be concerned simply to analyse public finances as they operated at the outbreak of war. With this context in place the thesis will proceed to outline the methods employed and the problems encountered by the Government in raising revenue to pay for the war. Finally, the thesis endeavours to appraise and criticise the techniques utilised mainly within the context of the constraints and nature of the financial system, but to some extend for their effects on the population and the course of economic growth over the period. It is written primarily from the discipline of economic history but inevitably and frequently passes into administrative and economic history. The questions raised could not be answered within the confines of a single discipline. My research cannot be offered as answers to a single question or set of hypotheses. The questions which underlie it are already stated. In so far as I have a single thesis or conclusion it is that, given the nature and constraints of the financial system, the Ministers, civil servants and their advisers responsible for providing the indispensable monetary means to obtain resources to prosecute the war, on the whole performed their task with commendable efficiency.